High-temperature solar steam generation by MWCNT-HfTe2 van der Waals heterostructure for low-cost sterilization. (April 2022) - Saleque, Ahmed Mortuza; Ahmed, Safayet; Ivan, Md. Nahian Al Subri; Hossain, Mohammad Ismail; Qarony, Wayesh; Cheng, Ping Kwong; Qiao, Junpeng; Guo, Zong Liang; Zeng, Longhui; Tsang, Yuen Hong
Abstract: Conventional steam sterilization for medical equipment requires electricity and significant initial capital cost, impeding its uses in many resource-constrained areas and exposing patients to nosocomial infections. The urgent need for a low-cost and environmentally friendly approach for the sterilization process can be addressed by utilizing abundant solar irradiance and an efficient solar absorber. Herein, for the first time, 1D–2D metallic MWCNTs and HfTe2 van der Waals heterostructure are used for realizing broadband solar absorption with an evaporation efficiency of 87.43% under one sun illumination resulting in an increase in steam temperature to 132 °C in < 20 mins. The facile fabrication process and minimalist design substantially reduced sterilization cost to only ¢0.21 per liter capacity. Furthermore, a proof-of-concept sterilizing demonstration resulted in a 99.04% reduction in E. coli bacteria, exceeding the requirements of the World Health Organization. Such a sterilization system would reduce 2.45 tons of CO2 emissions annually by substituting a 10 L capacity conventional autoclave. Hence, the MWCNT-HfTe2 @Cu foam-based medical sterilizing system could be a promising and low-cost sterilization solution in off-grid and resource constrained areas due to its superb sterilizing performance, dramatic capital and operating cost reduction capability, ease of maintenance, and a significant reduction in carbon footprint. Graphical Abstract: ga1 Highlights: 1st demonstration of novel 1D-2D metallic MWCNTs and HfTe2 vdW heterostructure for realizing broadband solar absorption. A low-cost (¢0.21 per sterilization per liter), faster and environment-friendly route for sterilizing medical equipment. Evaporation efficiency 87.43% under 1 sun, steam temperature raises to 132 °C in < 20 mins, reduced cooling time(< 4 mins). 30 mins of sterilization results in a 99.04% reduction of E. coli bacteria exceeding the sterilization requirement of WHO. Replacing 10 L capacity conventional autoclave with the proposed system would reduce CO2 emission by 2.45 tons per year.